2020
DOI: 10.3390/ijerph17176348
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Lack of Clinical Manifestation of Oral Mycosis and Systemic Diseases in Edentulous Patients Using Removable Prosthetic Restorations

Abstract: Objective: It is believed that oral infections can increase the risk of systematic diseases, such as atherosclerosis and coronary heart disease, stroke, chronic obstructive pulmonary disease, diabetes, cancer, rheumatoid arthritis, etc. It seems that oral invasive pathogens induce a systemic inflammatory response via mediators released by the cardiovascular system and liver, which increases the risk to the patient of these systematic infections, such as hypertension. On the basis of previous studies of the sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Candida-associated denture stomatitis was more com-monly found in denture-wearers with diabetes [23]. Underlying systemic diseases such as diabetes may mask the clinical symptoms of concomitant fungal infection of the oral mucosa in removable prostheses wearers [24]. Mycological examination may be used if in doubt [25].…”
Section: Diabetesmentioning
confidence: 99%
“…Candida-associated denture stomatitis was more com-monly found in denture-wearers with diabetes [23]. Underlying systemic diseases such as diabetes may mask the clinical symptoms of concomitant fungal infection of the oral mucosa in removable prostheses wearers [24]. Mycological examination may be used if in doubt [25].…”
Section: Diabetesmentioning
confidence: 99%
“…The study was conducted with 279 patients; 58% of patients with hypertension revealed no signs of inflammation. The onset of systemic diseases in edentulous patients wearing prosthetic devices and the subsequent use of medications to treat these diseases may lack clinical symptoms of simultaneous oral mucosal fungal infection [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…Oral infections are believed to increase the risk of systemic disease [ 44 , 45 ]. Oral invasive pathogens appear to induce a systemic inflammatory response through mediators released by the cardiovascular system and liver, increasing the risk of developing systemic infections [ 44 ]. The precise relationship between chronic diseases and mental disorders with oral diseases has not been fully clarified, and several theories have been proposed.…”
Section: Introductionmentioning
confidence: 99%